Effectiveness of a culturally attuned Internet‐based depression prevention program for Chinese adolescents: A randomized controlled trial. Issue 12 (13th September 2016) - Ip, Patrick; Chim, David; Chan, Ko Ling; Li, Tim M.H.; Ho, Frederick Ka Wing; Van Voorhees, Benjamin W.; Tiwari, Agnes; Tsang, Anita; Chan, Charlie Wai Leung; Ho, Matthew; Tso, Winnie; Wong, Wilfred Hing Sang
Abstract : Background: Depression prevention among adolescents is crucial for reducing the global disease burden. Internet‐based depression prevention approaches are found to be effective but they were mostly evaluated in a Western context. Grasping the Opportunity is a Chinese Internet intervention, which was translated and modified from CATCH‐IT developed in the West. We aimed to evaluate the effectiveness of Grasp the Opportunity in reducing depressive symptoms in Chinese adolescents. Methods: In this randomized controlled trial, Chinese adolescents aged 13 to 17 years with mild‐to‐moderate depressive symptoms were recruited from three secondary schools in Hong Kong. The participants ( n = 257) were randomly assigned to receive either intervention or attention control. The primary outcome was the improvement in depressive symptoms according to the revised Center for Epidemiologic Studies Depression Scale (CESD‐R) at the 12‐month follow‐up. Analyses were performed using intention to treat (ITT). Results: The participants were randomly assigned to receive the intervention ( n = 130) or attention control ( n = 127). Follow‐up data were obtained from 250 (97%) participants. Only 26 (10%) participants completed the intervention. Compared to the attention control, Grasp the Opportunity led to reductions in depressive symptoms at the 12‐month follow‐up with a medium effect size using ITT analysis (mean difference 2.6, 95% CI 0.59–5.55, effect size d = 0.36). Conclusions: Grasp the Opportunity is effective in reducing depressive symptoms in Chinese adolescents over a long follow‐up period. Poor completion rate is the major challenge in the study.